2014
DOI: 10.25100/cm.v45i1.1281
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and variability of dental morphology in deciduous and permanent dentition of a Nasa indigenous group in the municipality of Morales, Cauca, Colombia

Abstract: Objectives: To determine the frequency, variability, sexual dimorphism and bilateral symmetry of fourteen dental crown traits in the deciduous and permanent dentition of 60 dental models (35 women and 25 men) obtained from a native, indigenous group of Nasa school children of the Musse Ukue group in the municipality of Morales, Department of Cauca, Colombia. Material and methods: This is a quantitative descriptive, cross-sectional study that characterizes dental morphology by means of the systems for tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
2
17
0
6
Order By: Relevance
“…As observed in the current study, other researchers concluded that there is no evidence of sexual dimorphism in the meta cone, hypo cone, Carabelli's trait, parastyle, canine mesial ridge, labial convexity, shoveling, deflecting wrinkle, cusp 6/entoconulid and cusp 7/metaconulid when applying the ASUDAS method [15,28,[30][31][32]. Reality behind these findings may be, again, due to a low number of individuals in each subpopulation group (gender), including the present study.…”
Section: Discussion Of the Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As observed in the current study, other researchers concluded that there is no evidence of sexual dimorphism in the meta cone, hypo cone, Carabelli's trait, parastyle, canine mesial ridge, labial convexity, shoveling, deflecting wrinkle, cusp 6/entoconulid and cusp 7/metaconulid when applying the ASUDAS method [15,28,[30][31][32]. Reality behind these findings may be, again, due to a low number of individuals in each subpopulation group (gender), including the present study.…”
Section: Discussion Of the Resultssupporting
confidence: 65%
“…Scott and Turner fall within the group of researchers who claim that dental morphological characteristics are equally expressed between both sexes and that the sexual dimorphism exhibited by them is low or nonexistent. In studies of Goyes et al, [8] and Díaz et al, [28], both applied the ASUDAS method in the permanent dentition in different samples of the Colombian population, whose results demonstrated the absence of sexual dimorphism for the tuberculum dentale of the maxillary canines and the distal accessory ridge of the mandibular canines in the first study and, for cusp 5/metaconule for the second study mentioned. Such contradictory facts can reside on the assumption that in both cases the number of the sample was below the population of the present study, or that dental morphological characteristics are specific to a given population, or even because of the existing geographical distance separating population groups.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Dental anthropology, a subfield of biological anthropology, is the study of the development, eruption, number, size, morphology, modification, wear, and pathology of teeth, among other topics, in order to answer questions like how individuals and populations are related, what pre-historic humans' diet consisted of, and what their general health status was like [113]. According to Diaz et al [114], the analysis of dental morphology by anthropologists strives to understand how so-called Tooth Crown Morphological Traits present in frequency, sexual dimorphism, and bilateral symmetry in order to answer the aforementioned questions as well as give insight in biology, anthropology, dentistry, paleopathology, archeology, and forensic science.…”
Section: Dental Anthropologymentioning
confidence: 99%
“…Al estudiar las poblaciones indígenas Nasa [38], se puede afirmar que presentan la morfología dental propia del complejo dental mongoloide, que para el caso de la cúspide de Carabelli consistió en expresiones de fisura (grado 1) y fosa (grado 2), con mínimas expresiones de depresión en y (grado 3 y 4), y de cúspides pequeñas (grado 5), asociadas a posible mestizaje con mestizos caucasoides. Esta configuración en la frecuencia y la variabilidad, relaciona este grupo étnico directamente con los sinodontes, al igual que los demás grupos indígenas colombianos y americanos, hallazgos que son compatibles con lo referido en la literatura y que coinciden igualmente con la teoría sobre el origen mongoloide de los indígenas de América del Sur.…”
Section: Discussionunclassified
“…Fuente: modificado de http://cavern.uark.edu/~jcrose/dental/ que, según el teorema del límite central, una muestra se considera significativa a partir de 30 individuos [30]. La información sobre la frecuencia y variabilidad de la cúspide de Carabelli se obtuvo de dos publicaciones científicas (afrodescendientes de Tumaco y afrodescendientes de Guapi), y de las bases de datos de la Escuela de Odontología de la Universidad del Valle (mestizos caucasoides de Cali, afrodescendientes de Puerto Tejada, afrodescendientes de Villarica, indígenas nasa) [31][32][33][34][35][36][37][38].…”
Section: Materiales Y Métodosunclassified